TURKISH MYTHOLOGY AND EDUCATION - Rövşen ALİZADE (Fırat University, 2019)
Mythology can be regarded as the education system of the ancient human. Each event within the nature and community emerges as philosophical evidences that educate humans and prepare them to life. In this sense, mythology transformed into mythological information that stand for the reflection of reality. Therefore, mythology explains not the events, but the reasons of their occurrences, or in other words, does not depict the real world but makes it perceivable through symbols. Until the 19th Century, the Western World only acknowledged Greek Mythology when mythology was in question. However, as the researches progressed, it was set forth that all nations of the world and particularly Turkish nations have their own mythologies. In the 20th Century documentation of mythological theories and absorption of mythological systems gathered speed. These developments made the absorption of mythology also common in the circles of science around the world. In mythology, researching the beliefs pertaining to the cults of nature is a complex topic. Complexity of the topic is determined by the possibilities of approaching the problem from different aspects before each object. Nature constitutes the subject and context of mythological thinking. There are several different forms of beliefs related with the nature cults within the Turkish mythology. Also, there are several methods employed in examining the cults of nature. Utilization of different methods in the schools and movements within the area of social sciences paved the way for the emergence of various concepts also in researches on mythology, and brought in a rich methodological experience in both theoretical and practical terms in examining cults of nature. While this complexity and richness complicated the topic, on the other hand it also made it easy. In other words, while the plentitude of the possibilities in approaching the matter introduce difficulties to the researcher in selecting the method, it also provided the researcher with the opportunity to implement scientific conduct. This, in consequence, enabled the in-detail solution of the topic.